IMPLEMENTATION OF DISCOVERY LEARNING MODEL TO IMPROVE LEARNING RESULT OF NATURAL SCIENCE AT FIFTH GRADE OF SD N LELANG BANGGAI SUBDISTRICT - Kosmas Sobon (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
This research aims to descibe the improvement of student learning result in learning science by implementation of discovery learning model at fifth grade of SDN Lelang, Banggai Subdistrict. This research is a Classroom Action Research (CAR) in two cycles. Each cycle consisted of four steps namely planning, action, observation and reflection. The techniques of data collecting were test, interview, observation and documentation. The results showed that: (1) skill of teaching teacher in the first cycle 77,5% with good criteria and in second cycle obtained 86% with very good criteria; (2) student learning result in the first cycle 58,33% and the second cycle 83%. Based on the result of the research, it can be concluded that implementation of discovery learning model can improve Learning Result of Natural Science at Fifth Grade of SD N Lelang Banggai Subdistrict. Suggestions in this study was that:1) experimental methods could become as a teacher’s way to improve the quality of natural science learning in elementary school.2) in using discovery learning model, teacher have to follow stages well so that learning result can be successful.